War Crimes and Human Rights Violations through the Lens of Maqāṣid al-Syarī‘ah: A Normative and Ethical Analysis - Arminsyah Arminsyah; Siti Arifah Syam (KURAS Institute, 2025)
The crime of war is one of the most egregious violations of international humanitarian law and basic human rights (HAM), significantly affecting individual lives and global stability. From an Islamic perspective, human rights violations—especially in the context of armed conflict—can be analyzed through the lens of Maqāṣid al-Syarī‘ah, which seeks to protect five fundamental principles: religion (din), life (nafs), intellect ('aql), lineage (nasl), and wealth (mal). This research aims to examine war crimes from the perspective of Maqāṣid al-Syarī‘ah and evaluate the extent of human rights violations in warfare that contradict sharia values. Utilizing a qualitative approach and normative descriptive analysis of various international legal documents along with both classical and contemporary Islamic literature, this study concludes that war crimes—including mass killings, torture, rape, and the destruction of civilian infrastructure—directly undermine the primary objectives of sharia, which are to safeguard life and uphold human dignity. Ultimately, this research affirms that Islam categorically prohibits all forms of destructive violence against human values. Furthermore, Maqāṣid al-Syarī‘ah can serve as a normative framework for developing ethical solutions to war crimes on an international scale.